Human resource development theory and practice - Gold, Jeffrey; Holden, Rich; Iles, Paul (London Palgrave Macmillan, 2010)
"This book is a comprehensive and critical evaluation of the theory and practice of HRD. Ideally suited for undergraduates, it guides students through key contemporary topics. Written by a team of leading academic experts and packed with learning activities and real world examples, it is essential reading for any student studying HRD"--Provided by publisher.
Encountering HRD -- The nature and scope of HRD -- Strategic HRD and the learning and development function -- National HRD policies and practice -- Learning theories and principles -- The identification of training needs -- The design and delivery of training -- Evaluation of HRD -- Workplace learning and knowledge management -- Management development -- Leadership development -- Teams and team development -- HRD and diversity -- E-learning -- Contrasting contexts of HRD practice -- Continuing professional development and lifelong learning -- Graduates and graduate employment -- Corss-cultural HRD -- The future of human resource development.
Includes bibliographical references and index.
Keywords: Employees -- Training of; Personnel management